Microbial Quality of traditionally smoked Clarias gariepinus and Micromesistus poutassou in local markets in River state, Nigeria - Lukman Adegoke Agbabiaka; Olatunji Abubakar Jimoh; Gerald Ikenna Iwuagwu (Acta Scientiarum. Animal Sciences, 2025)
The present study evaluated microorganisms associated with traditionally smoked Clarias gariepinus and Micromesistus poutassou collected from three local markets (Mile One, Choba and Igwuruta) in Port Harcourt, River State, Nigeria. Bacterial and fungal analyses of the samples were carried out in the laboratory following standard procedures. The results showed wide variations in bacterial and fungal counts in smoked samples of C. gariepinus and M. poutassou collected from the three markets. Seven bacterial species (Bacillus cereus, Staphylococcus aureus, Enterococcus faecalis, Micrococcus luteus, Enterobacter sp, Escherichia coli, Salmonella sp,) were identified in the samples. In smoked catfish, total bacterial counts (4.2x105 cfu) were significantly (p < 0.05) higher in samples from Mile One Market while the least counts (1.64x105 cfu) was observed in samples from Igwuruta Market. Samples from Choba market recorded significantly higher coliform and Salmonella counts when compared with the values recovered from the other two markets. Similarly, E. coli growth was observed only in samples from Choba market at 3.90x103cfu. Based on public health concerns, the microorganisms identified in this study are causative agents of foodborne illnesses, hence the need to exercise caution in direct consumption of the fishes.